2015
DOI: 10.1007/s11695-015-1685-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Vitamin D Status After Roux-en-Y Gastric Bypass Surgery in Obese Patients Living in Northern Climate

Abstract: The prevalence of hypovitaminosis D before RYGB was comparable to patients living in the non-northern climate. Daily vitamin D intake meeting at least 2000 IU is associated with greater improvement in serum vitamin D concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…Figure 2 represents studies that have a number of participants of at least 50 per study group or subgroup, based on bariatric surgery type. It shows that mean 25(OH)D levels were ≤ 20 ng/ml in fifteen studies [5165], and between 20 and 30 ng/ml in the others [6677]. The weighted mean 25(OH)D levels (ng/ml) did not differ between studies, classified according to the baseline participants’ mean BMI (mean BMI ≥ 50 kg/m 2 , mean BMI between 45 and 50 kg/m 2 and mean BMI ≤ 45 kg/m 2 ) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2 represents studies that have a number of participants of at least 50 per study group or subgroup, based on bariatric surgery type. It shows that mean 25(OH)D levels were ≤ 20 ng/ml in fifteen studies [5165], and between 20 and 30 ng/ml in the others [6677]. The weighted mean 25(OH)D levels (ng/ml) did not differ between studies, classified according to the baseline participants’ mean BMI (mean BMI ≥ 50 kg/m 2 , mean BMI between 45 and 50 kg/m 2 and mean BMI ≤ 45 kg/m 2 ) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…These were divided into categories according to the type of the surgical procedure and the dose range of vitamin D supplementation. Only eight studies showed a mean 25(OH)D level > 30 ng/ml at 6 to 24 months post operatively [51,52,60,66,69,73,75,80]. Thirteen studies showed a mean 25(OH)D level < 20 ng/ml at 6 months to 11 years post operatively [51,54,55,64,78,8592].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations